Effect of the bus voltage level on the power system design for microsatellites - Mohammed Bekhti; Mohammed Beldjehem; Arezki Faiza (Institute of Advanced Engineering and Science, 2022)
Each time there is a need for a satellite mission analysis, engineers need to coordinate together the choice of one technology with regard to the other (i.e. solar cells technology, transistors, microcontrollers, and batteries). The process of selecting one technology to another or a component to another is called ‘trade off’. This concept is a hard and situational decision that involves diminishing one quality, of a system or a design in return for gains in other aspects such as weight, performance, speed and so on. The present paper will focus essentially on the use of the 28 V unregulated bus voltage because early satellites, all used, a 14 V unregulated bus voltage. The paper will also show trade-offs made when using the 28 V unregulated bus voltage with different topologies.